Media Permainan Tradisional sebagai Sarana Meningkatkan Minat Siswa SD Negeri 1 Palaan terhadap Permainan Tradisional - Aprilia, Chofifah Dwi; Shofiyulloh, Muhammad; Maulida, Azzahra; Setiawan, Achmad Yusuf (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
In the current era of globalization, all activities utilize technology, including children's games. Many game features are offered, both online and offline. It's no wonder that children are starting to leave traditional games and don't even know about traditional games. As a result of this increasingly rapid development of the times, traditional games are starting to be abandoned. In fact, traditional games have many benefits for the physical, emotional and cognitive development of children. Because of this, KKM Group 187 Bhaktikarya students want to preserve traditional games that have started to be abandoned. Our effort is to make traditional game media in the field of SD Negeri 01 Palaan. The research was conducted at SD Negeri 01 Palaan with a period of one week starting from January 2 -8 January 2022. The subjects in this research are 20 elementary school student which the 6 until 12 years old, consisting of 10 girls and 10 boys. After one week of the traditional game media being made, we observed several students starting to play with the media. They spend their free time playing engklek, gobak sodor, and egrang. In this way, children are indirectly starting to recognize and preserve traditional games which are starting to become extinct among today's children.